ANALISIS PENGELOLAAN KELAS DALAM MENINGKATKAN HASIL BELAJAR SISWA - Alviani Lingga Luthfika; Alifa Hunsussyifa; Valentina Silalahi (STKIP Subang, 2024)
The aim of this research is to analyze planning, implementation, supervision, as well as supporting and inhibiting factors in classroom management to improve student learning outcomes. This study used descriptive qualitative method. The data collection techniques used were interviews, observation, and documentation with the subjects being teachers and students in class IV B of SD Negeri Sempu 1, totaling 33 students. The results of this research show that classroom management is carried out by arranging facilities, students, and applying several principles of classroom management and continuous supervision, the supporting factors and inhibiting factors in classroom management are divided into internal and external factors.